A associação de mulheres agricultoras familiares de Santo Antônio do Sudoeste (PR) – sabores do leite: o processo de comercialização - Santos, Fabiane Zanini dos (2024)
This research aims to analyze the food marketing process of the Association of Family Farming Women of Santo Antônio do Sudoeste (PR) - Sabores do Leite, seeking to understand the historical process and its structuring, the main marketing circuits that they participate in, they way they sell and the importance of cooperation in achieving their objectives. Considering the gender issues that enhance and weaken the production and the marketing process of this association, we sought to build maps, graphs, and tables that visually demonstrate the quantity of production and the spatialization of Sabores do Leite Association. To achieve the objectives, interviews with the associated farmers were conducted and documents of the association were analyzed, such as minutes and the internal statute, in order to create graphic materials. This work is organized into three chapters. The first one addresses questions about the organizational structure of the association and the characterization of these women’s productions. The second one deals with the marketing processes and presents a deeper analysis of their two main forms: the fair and the National School Feeding Program (PNAE). The third and last chapter analyzes gender issues that are implicit in this entire process, from the formation of Sabores do Leite Association to the food marketing made by the group, as well as the achievements and obstacles of these women. Agribusiness and monoculture are increasingly present in rural areas. However, data from the 2017 Agricultural Census (IBGE) shows that the main source of food today, in Brazil, comes from family farming. For these food producers, the most important markets are short marketing circuits, such as fairs and direct sales, as well as public policy programs to encourage not only food acquisition but also its sale, such as Pnae. To form this association and strengthen its marketing and food production, in an environment dominated by patriarchy, this women’s organization faced several obstacles, but also achieved positive results. In this research, we recorded this process by telling the story and seeking to demonstrate the importance of this association for women’s lives, as well as for agriculture in the municipality. In this sense, the study of gender contributes to the analysis of existing inequalities between men and women, seeking to demonstrate the way in which patriarchy shapes society and affects the existence of these women.